The Common National Curriculum Base for Elementary Education: implications for teaching work (Olhar de Professor, 2022)
This article aims to analyze the curricular policy resulting from the National Common Curricular Base (BNCC) and the implications for the teaching work in Brazilian public basic education. It begins with analyzing documents from the Organization for Economic Cooperation and Development (OECD), the World Bank, bibliographic references, and legislation under the historical-dialectical perspective of how governments, political parties, and education entrepreneurs act to restore neoliberalism to the curriculum policy and the teaching work. Some implications of this curricular policy on the teaching work are increased workloads, precariousness, and devaluation in the context of control, surveillance, and accountability. If the BNCC can determine and standardize the curriculum, the pedagogical practices, and the teaching work, it can also transform and elevate education and human development to the pillars of the epistemology of praxis.
Keywords: Educaction. Common National Curriculum Base. Teaching Work.